Seres de contacto: la gestualidad en el Lisuarte de Grecia - Luna Mariscal, Karla Xiomara (El Colegio de México, 2019)
The paper analyses the presence and function of gestures in the Lisuarte de Grecia with particular attention to the role of the hand gestures, which are the most abundant in the text and constitute a metonymy of thekinesthetic of the novel. A study is made of the literary elaboration of gestures in the new conception of fiction proposed by Feliciano de Silva, in which entertainment and comedy play a key role. The paper offers a gestural typology of the novel and an analysis of the most frequent gestures